Land degradation zonation mapping of the protected forests based on Landsat TM Imagery and GIS approach - Santosa, Purnama Budi (2006)
Land degradation has been a major environmental issues posing threat to sustainability livelihood in semi arid and hilly region of Gunung Kidul, the south-east area of the Provinci of Yogyakarta, Indonesia. Considering that knowing extent and severity of the land is important as a decision support system to policy makers, resource managers as well as local communities and farmers, this study attempts to assess and to map land degradation severity of the protected forest in Gunung Kidul. For this purpose, Landsat TM Imagery was employed in this study to identify vegetation coverage, more specifically the vegetation density. In order to be able to identify this vegetation density, samples at different location were collected with handheld GPS. These samples are important input parameters for building regression equation that correlates between NDVI values and vegetation density. Together with the other input maps namely slope maps, erosion maps, and land management status maps, this vegetation density was then used to classify land degradation severity within GIS. The results show spatial distribution of different land degradation severity across the area in the forest. Most of the area are in severe and moderate condition at about 46.33 % and 42.42% respectively; whereas only very small area are in “not severe” condition at about 0.03%.